PRESENTASI DIRI PEMILIK DUA AKUN INSTAGRAM DI AKUN UTAMA DAN AKUN ALTER - Intris Restuningrum Pamungkas; Nuriyatul Lailiyah (Interaksi Online, 2019)
One of the most popular is one of the most popular. When someone asks about another person, they might have lots of questions about other people that will be asked to other people who will think about it or will be asked to people who make this a person who wants to know about others as if it is good enough before your opponent he spoke. The assessment of him is what ultimately makes the account owner in a special social media is Instagram that can be ordered compilation will be taken alone. Instagram unconsciously influences a person's insecurity which ultimately makes individuals needed to worry about any content that they poultry to meet certain standards. The existence of standards in social media makes a person feel unable to freely think whatever he feels and experiences because he will be afraid of being judged by others for the content they have on poultry on a special social media, which makes every individual can construct Different identities on the same account that is instgaram or in other words have more than one account on the same social media but have a different identity on each account that it uses. This study shows the stage used on the main account and the stage used by the owner on his alter account, thus creating a different identity on each account. The theory used in this study is Dramaturgi's theory in which the account owner represents an actor who is playing his role on Instagram social media.